An Introduction to Revisiting Development Studies Education and an Invitation to Rethink Teaching, Learning and Knowledge Production in the Neoliberal University. (July 2022) - Patel, Kamna; North, Amy
We are at a moment of growing critical self-reflection in the field of development studies—heightened by debates on decolonization—that is opening up difficult conversations on teaching, learning and knowledge production for development studies education. This special issue augments these conversations and revisits development studies education within the context of the 'neoliberal university'. It is our contention that we cannot engage with the expansive project of rethinking development studies education, without elaborating on higher education institutions (HEIs) as the site where change is mediated, managed and resourced. The articles in this volume give empirically grounded and interrelated narratives that elucidate the relationships between development studies and the neoliberal university from a range of disciplinary and geographical perspectives. They allow us to make two salient contributions, firstly, on the role of HEIs as a site of engagement and entanglement between development practice and development studies, and secondly, on the ways in which the neoliberalization of higher education shapes development studies pedagogy. It is our hope that these articles are read as a timely intervention and invitation to rethink development studies education in this context.